The Progressive Muscle Relaxation and Deep Breathing as Effective Procedures in Reducing the Stress Levels on Older People - Rizky Erwanto; Fajarina Lathu Asmarani (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2018)
The world population and proportion of elderly people at present are increasing. The increasing population of the elderly people needs special attention because elderly people included in the group of a population at risk. A population at risk is the group with certain characteristics that able to generate health issues. The changes in physical capability are able to influence the entire body’s functions and capabilities. One of the occurring changes is the aging process embodied as psychosocial changes. The psychosocial changes also able to induce a stress in elderly people. One of the complementary and alternative nursing management is through the therapies of a progressive muscle relaxation and a deep breathing. Progressive muscle relaxation and deep breathing do not cause side effects, do not require additional cost, and can be performed individually as well as do not require routine training from the instructor, able to reduce the heart rate and able to relax the body. These interventions can be done by nurses or caregivers in service institutions or nursing home which performed in accordance with the determined SOP (Standard Operational Procedure). This research is aimed to determine the effectiveness of progressive muscle relaxation and deep breathing to reduce the stress on elderly people in the Hanna Nursing Home Yogyakarta. There were 40 elderly people who live in Hanna Nursing Home involved in this study. This research method was a Quasi Experimental design with pre and post test without control group design. The sample tehcnique in this study was quota sampling which considers either inclusive or exclusive criteria. The instrument of the study was DASS instrument to measure the stress levels of elderly people. The measurement results of the stress function of elderly people through the utilization of DASS show that there was a decline of mean value in about 4.4 points. From the paired t-test, 0.000 p-values were acquired. The results of the bivariate test by using the DASS instrument showed that the interventions of progressive muscle relaxation and deep breathing in reducing the stress of elderly people in Hanna Nursing Home Yogyakarta were effective.  Keywords: the progressive muscle relaxation, deep breathing, stress, elderly people